Investigation of microstructure and mechanical properties of explosively welded ITER-grade 316L(N)/CuCrZr hollow structural member - Ma, Rui; Wang, Yaohua; Wu, Jihong; Duan, Mianjun (Fusion engineering and design, 2015)
•Develop a new explosive welding method to fabricate the hollow structural member.•Effects of solution annealing on microstructure of welding interface researched.•Influence of heat treatments on hardness evolution in welding interface studied.•The ultimate strength and elongation were increased after solution annealing.•The interface of samples was exhibited ductile fracture after solution annealing. In this study, a new explosive welding method furnished an effective way for manufacturing ITER-grade 316L(N) stainless steel/CuCrZr alloy hollow structural member. In order to recover some hardening effects, caused by plastic deformation during explosion welding in the materials bonding interface region, the welded samples were subject to the solution annealing (SA) treatment at 970°C for 30min. The SA heat-treated samples were then aged at 580°C for 2h. Optical microscopy (OM) and electron microscopy (SEM) were used to analyze the microstructure of bonding interface. Energy dispersive spectroscopy (EDS) analysis was performed to investigate the diffusion zone formed in the interface region after the solution annealing (SA) treatment. Moreover, the mechanical properties of the welded samples were evaluated through microhardness test and tensile strength test. Microstructural analysis showed that the welded sample had a wavy interface, and there was no melting zone and intermetallic layer formed in the interface. The result of microhardness test revealed an increase in hardness for both sides near to the bonding interface; this is due to more severe plastic deformation in these regions during the explosive welding. After the tensile test, obvious necking was observed in the fracture cross section of samples. SEM observation indicated that the samples with the post solution annealing treatment exhibited a ductile fracture with dimple features after tensile test.